(untitled) (Revista Archai, 2024)
It is a commonplace in our histories of Greek philosophy that the first thinker to fashion deductive arguments was Parmenides of Elea. One corollary of this view is that Ionian philosophers before Parmenides provided no arguments in support of their views. In what follows I offer a critique of this dismissive characterization, focusing on the first thinker for whom we have a substantial body of evidence, Xenophanes of Colophon. Specifically, Xenophanes argued that retelling the old stories of divine strife and warfare was out of keeping with the qualities of cleanliness and purity considered essential to a proper symposium. He held also that the presence of fossilized remains at inland and mountainous locations was best explained by positing cycles of worldwide flooding and drought, and he linked many other phenomena with the presence of earth and/or water. He also distinguished between having direct perceptual access to events and knowing the clear and sure truth about them, and concluded that about far-off matters such as the gods and the nature of all things no man can know the certain truth. He held also that a series of contrasts between divine and human attributes followed from an initial assumption of divine greatness.